Gender role identity and gender intensification: Agency and communion in adolescents' spontaneous self-descriptions. Issue 1 (2nd January 2022) - Korlat, Selma; Foerst, Nora Maria; Schultes, Marie-Therese; Schober, Barbara; Spiel, Christiane; Kollmayer, Marlene
ABSTRACT: In line with gender stereotypes, girls are expected to take on communal roles and boys to take on agentic roles. Based on gender intensification theory, the present cross-sectional study investigated girls' and boys' gender role identity and corresponding age differences across adolescence using the spontaneous self-description method. In total, 3423 adolescents aged between 11 and 15 years were asked to describe themselves with three attributes later coded in terms of agency and communion. ANOVA results showed expected but small gender differences in agency and communion, and no evidence for gender intensification. Moreover, significant gender differences were found in only 17% of the named attributes. The results thus indicate greater gender similarities than gender differences in adolescents' self-descriptions.